Design Performances: How Organizations Inscribe Artifacts to Change Routines - Glaser, Vern L. (Academy of Management Journal, 2017)
Organizations often create and employ artifacts in order to change their routines, but little is known about how artifacts can be designed to intentionally influence routine dynamics. In this paper, I present findings from an inductive, ethnographic study of how a law enforcement agency fabricated a game-theoretic artifact to modify its patrolling routine. Based on my in-depth analysis of the actions associated with creating this game-theoretic artifact, I develop a theoretical model that shows how organizational actors iteratively engage in a series of design performances to envision new sociomaterial assemblages of actors, artifacts, theories, and practices. These design performances influence routine dynamics by both eliciting mechanisms of abstracting grammars of action, exposing assumptions, distributing agency, and appraising outcomes, and by creating new assemblages that can be deployed in future routine performances. By revealing the generativity of design performances and sociomaterial assemblages, this empirical study contributes to our understanding of routine dynamics, performativity, and strategy tools.